Kr̨̄op kāndamn̄œn ngān kānčhat kānsưksā samrap phūmī khwāmt̨ongkān phisēt (Klum Ngān Patirūp Kānsưksā Khan Ph̄ưnthān, Samnakngān Khana Kammakān Kānsưksā h̄æng Chāt, Samnak Nāyok Ratthamontrī, 2000)
Outlines the rationale for inclusive education and explores the key issues in bringing it to reality. Could be used with educational personnel, administrators, teacher educators, teachers and student teachers, as well as parents and community groups.